La gestión del Talento Humano en la Cooperativa Cacha Ltda, y su incidencia en el desarrollo institucional período julio 2014, julio 2014. - Cando Tiñe, José Miguel (2016)
Human Resource Management is composed of individuals and organizations. Individuals or as we call partners are key factors to success or failure, they are guided by the administrator who has the obligation to show the path that will lead to success. Every organization should have a management plan on human talent, starting from the entry of personnel where it is sought, to choose and select the candidate with unique abilities and skills that each possesses, the administrator is responsible for the constant training collaborator evaluation to determine their strengths and weaknesses therefore they receive rewards to motivate, strengthen fellowship, teamwork, of all people regardless of the position they play each. A trained staff enables institutional development, it is essential to be adequately staffed, motivated, in each area as they are the only actors that can reach to realize the objectives of the organization. When referring to the term of the objectives it is essential that the organization draw up clear, precise, measurable and most important objectives to serve as motivation for staff. Another factor is the resources; the working environment in which they operate in the quality of this climate directly influences the satisfaction of the people and therefore productivity. In brief, organizations are formed by people and depend on them to achieve their goals and fulfill their mission that is why the human talent plays an important role so today is considered the most precious asset that organization has.